The legal framework and implementation of baby hatch in Malaysia / Muhammad Affiq Parthi, Muhammad Hilmi Hashim and Zulhilmi Zabri - Parthi, Muhammad Affiq; Hashim, Muhammad Hilmi; Zabri, Zulhilmi (Faculty of Law, 2013)
This research would focus on the legal framework and implementation of Baby Hatch in Malaysia. The reason for us to take on a journey upon such research is due to the fact that there are no single law or regulation governing the administration of Baby Hatch in Malaysia. Our research is an attempt to explain why Malaysia need such system to manifest itself, in comparisons with Baby Hatch's laws around the globe such as those implemented in the United States of America, Japan and Germany. In Malaysia, the only law governing abandoned babies are the Penal Code, Child Act 2001 and the Adoption Act. It is provided under the Penal Code that the act of a mother or birthparents abandoning a child under the age of twelve years old is a criminal offence. It further states that abandonment must occur at unsafe places in order for the mother or the birthparents to be prosecuted upon successful charges. However, it does not specifically provide as to what construe 'unsafe places', does Baby Hatch considered as unsafe place? Hence, the main aim of this research is to clarify any vague areas in the nation's legal context. Apart from that, the laws governing adoption in Malaysia is immensely procedural and swarming with bureaucracy, making an application to apply for citizenships for these unfortunate babies a tedious job. Hence, by suggesting how Malaysia can improve its adoption processes, we hope to expedite the departure of these babies to a loving and caring family.